Two cities, two stages in transforming society—a mixed methods study comparing doctors’ adoption of mobile apps for communication with patients in Hangzhou and Yancheng, China - Chen, Dongjin; Su, Zhenhua; Gu, Zheng (Frontiers in Public Health, 2024)
Objectives: Mobile apps have become commonplace in doctor-patient communication over the last twenty years. Doctors mainly use two kinds of app, social networking apps (i.e. WeChat) and medical platform apps (i.e. Haodf). The purpose of this study was to investigate whether the attributes of social interaction in local society impact doctors' choice of mobile apps to communicate with patients. This article addresses two research questions: (a) To what degree do doctors' adoption patterns in different societies differ? (b) Why do doctors choose certain mobile apps to communicate with patients? Methods: This study employed a mixed methods research design to analyze doctor's adoption behavior patterns in two cities, Hangzhou (HZ) and Yancheng (YC), which represent two stages in a transforming society. Various patterns, measured as the percentage of doctors who utilize the medical platform app ofHaodf among all doctors and the average service counts per doctor, were compared in three groups of tertiary hospitals: the top ones in HZ, the average ones in HZ, and the average ones in YC. We also conducted thematic content analysis of qualitative data from semi-structured interviews with 20 purposely selected doctors in the two cities.The percentages of doctors who have adopted the app of Haodf from the three groups of tertiary hospitals were 49.97%, 41.00%, and 32.03%, with an average service counts per doctor of 261,182 and 39, respectively. According to the interviewees, doctors from YC are more likely to use social networking apps to communicate with patients than their HZ counterparts to maintain social connections with their relatives, friends, colleagues, and others.This study demonstrates that doctors' choices of mobile apps are dependent upon social context. In traditional society, where people have close ties, the logic of using social networking apps lies in doctors' need to maximize the utility of their knowledge by maintaining social connections with others. In modern society, where the close ties between people have gradually weakened, the logic of using medical platform apps lies in doctors' needs for reputation marketing, either for themselves or for institutions, their affiliated departments or hospitals.